Impact of aquatic antibiotic pollution on Pseudomonas aeruginosa resistance (Revista Sistemas de Producción Agroecológicos, 2025)
The excessive and improper use of antibiotics has led to the presence of these substances in water resources, triggering the development of antimicrobial resistance in bacteria of relevance to public health, such as Pseudomonas aeruginosa. This opportunistic pathogen, known for its intrinsic resistance, can cause infections in humans, animals and plants. Worldwide, different concentrations of antibiotics have been detected in fresh water, and according to evidence even in subinhibitory concentrations. Pseudomonas aeruginosa is capable of developing mutations in genes related to porins, efflux pumps and enzymes; in addition, it has the ability to acquire resistance genes, generate persistent cells and form highly organized communities, known as biofilms, which function as protective shields. These resistances, both acquired and adaptive, are caused by the presence of antimicrobial agents, the selective pressure exerted and environmental factors. It is important to highlight that the adaptation of Pseudomonas aeruginosa to freshwater contamination with antibiotics is a crucial issue in the surveillance and management of environmental pollution. This is essential to prevent the spread of bacterial resistance, protecting both human health and environmental balance.
Keywords: Antimicrobial resistance; Aquatic environment; Resistance genes